Myocardial fibrosis in aortic stenosis: comparison between clinical data, laboratory, echocardiography, and cardiac magnetic resonance - Tosto, Giuseppe; Passaniti, Giulia; Gibiino, Fortunata Alessandra; Deste, Wanda; Indelicato, Antonino; Torrisi, Tito; Bottaro, Giuseppe; Cannizzaro, Maria Teresa; Tamburino, Corrado (Journal of Cardiology and Cardiovascular Medicine, 2023)
Introduction: Patients with aortic stenosis often develop hypertrophy and fibrosis, regardless of symptoms. Cardiac Magnetic Resonance (CMR) represents the gold standard for the evaluation of fibrosis despite numerous limitations: cost, availability, atrial fibrillation, claustrophobia, kidney failure or inability to apnea. Purpose: The aim is to validate the role of echocardiographic parameters, such as Global Longitudinal Strain (GLS), as early markers of fibrosis. Clinical and laboratory data, particularly B-type Natriuretic Peptide (BNP), were also analyzed. Material and methods: In our study we recruited 33 patients with severe aortic stenosis, correlating echocardiographic values of GLS with the qualitative analysis of Late Gadolinium Enhancement (LGE) and the quantitative analysis of T1 mapping of CMR. Results: 70% of patients with an alteration of GLS had LGE+. Univariate logistic regression shows that the factors associated with the presence of LGE on CMR are hypertension (p = 0.043), GLS (p = 0.032), and elevated BNP values (p = 0.021); for GLS, Odds Ratio (OR) is 5 so the chance of finding fibrosis on CMR increases 5 times in presence of an altered GLS. The multivariate analysis confirms the association with impaired GLS values (p = 0.033) and hypertension (p = 0.025), but not with elevated Pro-BNP values. Conclusion: In patients with severe aortic stenosis, the association between GLS, LGE, and T1 mapping can help identify earlier those patients with structural changes caused by the disease, who could benefit from early intervention. It remains to be established how the presence of these alterations has a role in determining the intervention time and the outcome of these patients.